CD163 Monoclonal Antibody Modified Polymer Prodrug Nanoparticles for Targeting Tumor-Associated Macrophages (TAMs) to Enhance Anti-Tumor Effects - Zun Yang; Haijiao Li; Wenrui Zhang; Mingzu Zhang; Jinlin He; Zepeng Yu; Xingwei Sun; Peihong Ni (MDPI AG, 2023)
Tumor-associated macrophages (TAMs)-based immunotherapy is a promising strategy. Since TAMs are mainly composed of M2-type macrophages, they have a promoting effect on tumor growth, invasion, and metastasis. M2-type macrophages contain a specific receptor CD163 on their surface, providing a prerequisite for active targeting to TAMs. In this study, we prepared CD163 monoclonal antibody modified doxorubicin-polymer prodrug nanoparticles (abbreviated as mAb-CD163-PDNPs) with pH responsiveness and targeted delivery. First, DOX was bonded with the aldehyde group of a copolymer by Schiff base reaction to form an amphiphilic polymer prodrug, which could self-assemble into nanoparticles in the aqueous solution. Then, mAb-CD163-PDNPs were generated through a "Click" reaction between the azide group on the surface of the prodrug nanoparticles and dibenzocyclocytyl-coupled CD163 monoclonal antibody (mAb-CD163-DBCO). The structure and assembly morphology of the prodrug and nanoparticles were characterized by 1H NMR, MALDI-TOF MS, FT-IR UV-vis spectroscopy, and dynamic light scattering (DLS). In vitro drug release behavior, cytotoxicity, and cell uptake were also investigated. The results show that the prodrug nanoparticles have regular morphology and stable structure, especially mAb-CD163-PDNPs, which can actively target TAMs at tumor sites, respond to the acidic environment in tumor cells, and release drugs. While depleting TAMs, mAb-CD163-PDNPs can actively enrich drugs at the tumor site and have a strong inhibitory effect on TAMs and tumor cells. The result of the in vivo test also shows a good therapeutic effect, with a tumor inhibition rate of 81%. This strategy of delivering anticancer drugs in TAMs provides a new way to develop targeted drugs for immunotherapy of malignant tumors.